Mobile School And Educational Sustainability In Nigeria - Ogunode, Niyi Jacob (International Journal on Integrated Education, 2026)
The article discusses the importance of integrating mobile schools into Nigeria's educational system. It is a strategic paper. The paper makes use of secondary data. Print and online publications supplied the secondary data. As to the study, some of the advantages of integrating mobile schools into Nigeria's educational system includes increased availability of education, encouraging diversity and inclusion, flexible and cost-effective learning, disaster response, and integration of technology. The study recommends the Federal Ministry of Education formally integrate mobile instruction into the national education policy in accordance with these findings, ensuring certain that it is recognized, promoted, and supervised as an aspect of the Universal Basic Education (UBE) framework. Sufficient money ought to be made aside by the government and development partners to establish and sustain mobile schools, including funding the provision of instructional materials, transport, and teacher incentives. To give teachers the skills and flexibility needed to thrive in mobile learning contexts and work alongside nomadic or displaced populations, specialized training programs need to be developed.